Influence of ceramic primers on microshear bond strength between resin cements and zirconia-based ceramic - Valéria Bisinoto Gotti; Saturnino Calabrez Filho; Gilberto Antônio Borges; Luciano de Souza Gonçalves (Universidade Estadual de Campinas, 2015)
Aim: This study evaluated the effect of a coupling agent ceramic primer (CP) on the microshear bond strength (ìsbs) between luting cements and zirconia-based ceramic. Methods: Zirconia discs (Cercon) were made and finished with silicon carbide paper and submitted to air abrasion using 50 µm aluminum oxide particles (Al2 O3 ) under 4 bar pressure. Zirconia disks were randomly assigned to four groups (n=10): (G1) ResiCem luting cement + Porcelain Primer, (G2) ResiCem luting cement only, (G3) Clearfil Esthetic Cement + Clearfil Ceramic Primer and (G4) Clearfil Esthetic Cement only. The luting cements were prepared according to manufacturers' recommendations and inserted in an elastomeric mold positioned onto a zirconia disc. Each specimen was photoactivated by 20 s. The specimens were stored at 100% relative humidity and 37ºC for 24 h. The ìsbs test was performed using universal testing machine at a crosshead speed of 0.5 mm/min. An optical microscope was used to analyze the failure modes and illustrative images were captured with a scanning electron microscope. The ìsbs data were analyzed by two-way ANOVA (p<0.05). Results: No significant difference was found among the four groups G1 (17.4±6.8), G2 (17.1±5.5), G3 (15.6±5.5) and G4 (14.2±3.5), all of which showed 100% of adhesive failures. Conclusions: CP showed no increase in the ìsbs between zirconia-based ceramic and resin luting cements.